PADMKSDPWM PERAN ACARYA DALAM MENINGKATKAN KARAKTER SISWA DI PASRAMAN WIDYA MARGA DESA MENDALANWANGI KECAMATAN WAGIR KABUPATEN MALANG PROVINSI JAWA TIMUR: PERAN ACARYA DALAM MENINGKATKAN KARAKTER SISWA DI PASRAMAN WIDYA MARGA DESA MENDALANWANGI KECAMATAN WAGIR KABUPATEN MALANG PROVINSI JAWA TIMUR - Mistriani; Sumantra, I Nengah; Giri, I Putu Agus Aryatnaya (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
Hindu religious education can be done through formal and non-formal education. One of the non-formal educations is at the pasraman, where Acarya plays an important role in improving the character of students. The role of the Acarya is to shape the behavior of students who were previously not good to be good, and those who were previously good to be even better. The issues that will be discussed include 1) How is the learning process by Acarya in improving the character of students at the Widya Marga Pasraman?; 2) How is the Hindu Religion learning method in improving the character of students at the Widya Marga Pasraman?; and 3) What are the obstacles faced and efforts made to overcome obstacles to learning Hinduism in improving the character of students at the Widya Marga Pasraman? This study aims to determine the learning process carried out by Acarya in improving the character of students at the Widya Marga Pasraman, Hindu Religion learning methods in improving the character of students at the Widya Marga Pasraman, and the obstacles faced and efforts made to overcome the obstacles to learning Hindu Religion in improving character students at the Widya Marga Pasraman. The characters in question are religious character, tolerance, social care, environmental care, responsibility, and honesty. The theory used to analyze the problem is social learning theory from Albert Bandura and behavioristic theory from Skinner. The data collection methods are non-participant observation, unstructured interviews, literature studies, and document studies. The data that has been collected was analyzed using a qualitative descriptive analysis method with reduction steps, data presentation, and drawing conclusions. The results of the study show that Acarya's role in improving student character has gone well where Acarya is a source of knowledge, role model, and motivation. Acarya uses several methods in the learning process, namely the Sad Dharma method. Obstacles faced in improving student character include external and internal factors which are anticipated by innovating to make media independently and applying a personal approach (Upanisad). Keywords: Pasraman, Acarya, Character, Sad Dharma.